Comparative Cultural Geography: Empirical evidence on processes of integration in rural Bolivia, Ivory Coast and Indonesia - Faust, Heiko (ERDKUNDE, 2006)
In many tropical countries, areas of natural forest are currently being further cleared and cultivated in order to offer opportunities for development to a growing population. The question arises as to how the migrants affect local structures within the context of their cultural, social and economic activities and hence influence the use of land. In order to examine this question, it is necessary to consider how socio-cultural co-existence and economic relations in the settlements between migrants of differing origins and ethnic groups manifest themselves. Therefore this article compares processes of integration in selected settlement areas in Bolivia, Ivory Coast and Indonesia. The comparative study is based on an empirical survey, which is geared to the sociological theory on integration. The approach follows ESSER's concept of Integration (2001) which formulates clear criteria for the analysis. According to these criteria, aspects of systems integration (economy, politics, societal community, fiduciary system) are considered on the one hand, whilst on the other hand, integration within the social structure is analysed on the basis of four categories (cultural adaptation, positioning, interaction, identification). It can be shown that the processes of migration in the selected areas are similar and the general cultural, national and regional conditions essentially reveal few differences. The expectation that the processes of integration would differ due to the general conditions of the national and regional cultural areas in Bolivia, Ivory Coast and Indonesia, has not been confirmed. Furthermore, it has been clearly demonstrated that non-integration has negative consequences for the use of resources. The general assumption that ethnic homogeneity tends to have an integrating effect, while heterogeneity initiates non-integration is underlined by this study. It is explained that the research villages can be classified on the basis of their demographic structure, the processes of integration and ethnic stratification, largely independently of their location in a cultural area.